Light Attraction in Carabid Beetles: Comparison Among Animals From the Inner City and a Dark Sky Reserve - Kaunath, Vera; Eccard, Jana A. (Frontiers in Ecology and Evolution, 2022)
Artificial light at night (ALAN) is altering behaviour of nocturnal animals in manifold ways. Nocturnal invertebrates are affected in particular, based on their fatal attraction to ALAN. This selective pressure has the potential to evolve the flight-to-light response in insects, as shown recently in a moth species. Here we investigated light attraction in ground beetles (Coleoptera: Carabidae) comparing among animals captured at a grassland in the centre of Berlin with high light pollution (HLP) levels experienced for many decades, to animals collected at a low-polluted area in a Dark Sky Reserve (DSR), using odour bait. We used animals from 8 species from 3 genera, which occurred at both sites, controlling for genus, ecotype, trapping time, time in captivity. Across all genera, in an arena setting at night, HLP beetles (n=75) showed a reduced attraction towards ALAN, and during daytime, were less active in an open field test, compared to DSR (n=143). In the most common species Calathus fuscipes (37+118 individuals) meanwhile, results were not confirmed, indicating that not all species are equally affected. Reduced attraction to ALAN in urban beetles may either be a result of phenotypic selection in every generation removing HLP individuals that are attracted to light, or an indication for ongoing evolutionary differentiation among city and rural populations in their light response. A reduced attraction to light sources may directly enhance survival and reproductive success of urban individuals. A general decrease in mobility may though negatively influence dispersal, reproduction and foraging success, emphasises the selective force that light pollution can have by shaping and modifying behavioural of insects.